A Metabolomic Approach to Investigate the Effect of Phytonutrients on Proteostasis and Metabolic Pathways in Drosophila melanogaster - Mikropoulou, Eleni V.; Evangelakou, Zoi; Trougakos, Ioannis P.; Halabalaki, Maria (Planta Medica, 2024)
The use of Drosophila melanogaster as a biological platform to study the effect of diet and food bioactives on the metabolome remains a highly unexplored subject. Aiming to establish alternative solutions for the investigation of nutritional interventions with bioactive natural products by employing LC-MS-based metabolomics approaches, we assessed the effect of a phytonutrient-rich extract from the endemic Mediterranean plant Cichorium spinosum (stamnagkàthi) on a Drosophila population. The extractʼs modulating effect on the proteostasis network and metabolism of young D. melanogaster flies was evaluated. Furthermore, an untargeted metabolomics approach, employing a C18 UPLC-ESI-Orbitrap-HRMS/MS platform, permitted the detection of several biomarkers in the metabolic profile of Drosophila’s tissues; while targeted amino acid quantification in Drosophila tissue was simultaneously performed by employing aTRAQ labeling and an ion-pairing UPLC-ESI-SWATH-HRMS/MS platform. The detected metabolites belong to different chemical classes, and statistical analysis with chemometrics tools was utilized to reveal patterns and trends, as well as to uncover potential class-distinguishing features and possible biomarkers. Our findings suggest that Drosophila can serve as a valuable in vivo model for investigating the role of bioactive phytoconstituents, like those found in C. spinosum’s decoction, on diverse metabolic processes. Additionally, the fruit fly represents a highly effective platform to investigate the molecular mechanisms underlying sex differences in diverse aspects of nutrition and physiology in higher metazoans.
Keywords: Cichorium spinosum; Asteraceae; Drosophila melanogaster; amino acids; metabolomics; Orbitrap; TripleTOF; proteostasis network